Chemical composition and repellent activity of methyl cinnamate-rich basil (ocimum basilicum) essential oil - Hamid Nour, Azhari; Idris, Abeer A.; Ishag, Omer Adam; Nour, Abdurahman Hamid (Turkish Chemical Society, 2022)
Basil (Ocimum basilicum L.) is an important culinary herb and essential oil source widely recognized worldwide. The oil of the plant is beneficial for medicinal uses, and it has many biological activities such as insect repellent, larvicidal, and bactericidal. This study aimed to investigate basil's essential oil for its chemical composition and repellent activity. The essential oil of basil was extracted from fresh leaves by steam distillation method, and the chemical composition of the oil was determined by using GC/MS. Also, the repellent activity of the oil was tested against American cockroaches. Ebeling Choice-Box test with a little modification used in repellence test. The obtained results of chemical composition revealed that the amount of the oil contained forty-one chemical constituents (~97.1%); the major constituents were methyl cinnamate (25.3%), linalool (19.1%) and estragole (12.3%) as the major oxygenated monoterpenes. While α-bergamoten (5.3%), germacrene (4.6%), γ-cadinene (2.8%), and β-elemene (2.4%) were the main compounds in sesquiterpene hydrocarbons. Whereas, in oxygenated sesquiterpenes, Tau-cadinol (4.3%) was an important compounds and ocimene the highest compound in monoterpene hydrocarbons. The obtained results also indicated that the essential oil had good activity against the P. American, at a 100% concentration of oil; the repellence reaches 100% after 1 h. The IC50 and IC90 values of basil essential oil against P. Americans were 53.0 and 83.0%, respectively. The major compound methyl cinnamate which exists in basil essential oil is a very important compound and could be used in a wide area of industrial applications as repellent products, medicinal products, and cosmetics.